Congenital erythropoietic porphyria in an Indian Child - Archana Singal; M N Kayarkatte; Deepika Pandhi (Wolters Kluwer Medknow Publications, 2019)
Congenital Erythropoetic Porphyria (CEP) also called the "Günther disease", is a rare variant of porphyria. It is caused by the deficiency of uroporphyrinogen III synthase (URO-III-synthase), an enzyme in the heme biosynthetic pathway. Clinically, CEP presents with blistering over face and extremities, scarring, hypertrichosis and dyspigmentation. Acral blistering leads to mutilation of the fingers with acro-osteolysis of distal phalanx We, hereby, report an 8-years-old boy with classical clinical features and porphyrin assays.